Screening red foxes (Vulpes vulpes) for possible viral causes of encephalitis. Issue 1 (December 2016) - Bourg, Manon; Nobach, Daniel; Herzog, Sibylle; Lange-Herbst, Hildburg; Nesseler, Anne; Hamann, Hans-Peter; Becker, Sabrina; Höper, Dirk; Hoffmann, Bernd; Eickmann, Markus; Herden, Christiane
Abstract Background Next to various known infectious and non-infectious causes, the aetiology of non-suppurative encephalitis in red foxes (Vulpes vulpes ) often remains unclear. Known causes in foxes imply rabies, canine distemper, toxoplasmosis, Aujeszky's disease, as well as parvovirus, adenovirus, circovirus and flavivirus infections. In this study, particular attention was paid on bornaviruses, since red foxes are predators of bicoloured white-toothed shrews, a reservoir of Borna disease virus 1 (BoDV-1). In addition, foxes are known to be highly susceptible for viruses of the orderMononegavirales . Methods Analyses for the presence of anti-BoDV-1 antibodies, BoDV-1-RNA and antigen were performed on 225 blood and 59 brain samples, from a total of 232 red foxes. Foxes originated from BoDV-1 endemic and non-endemic German areas. Additional investigations for the presence of rabies, canine distemper, toxoplasmosis, Aujeszky's disease, parvovirus, adenovirus and flavivirus infections were carried out on 16 red foxes with non-suppurative (meningo-) encephalitis. A metagenomic analysis was used on three representative brain samples displaying encephalitis. Results Among 225 foxes, 37 displayed anti-BoDV-1 antibodies with titres ranging between 1:40 and 1:2560, regardless of geographic origin. In 6 out of 16 foxes with encephalitis, canine distemper virus was detected. No evidence of any of the other investigated agents was found in the 16 fox brains with encephalitis. Metagenomics revealed no infectious agents, except for one already known canine distemper case. Conclusion Red foxes can exhibit BoDV-1 specific antibodies without association with geographic origin or encephalitis due to bornavirus infection. The encephalitis pattern was highly conspicuous for a viral infection, but remained unclear in 10 out of 16 foxes. Thus, presently unknown infectious and non-infectious causes need to be considered and further investigated, especially since foxes also tend to occur in human proximity.